2022
DOI: 10.1101/2022.08.19.504521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunopeptidomics-based design of highly effective mRNA vaccine formulations againstListeria monocytogenes

Abstract: Listeria monocytogenes is a foodborne intracellular bacterial pathogen leading to human listeriosis. Despite a high mortality rate and increasing antibiotic resistance no clinically approved vaccine against Listeria is available. Attenuated Listeria strains offer protection and are tested as antitumor vaccine vectors, but would benefit from a better knowledge on immunodominant vector antigens. To identify novel antigens, we screened for Listeria epitopes presented on the surface of infected human cell lines by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…The use of an adjuvant led to the activation of invariant natural killer T (iNKT) cells and specific T cell responses. Experiments showed that immunization with the top vaccine candidate, LMON_0149, was able to confer protection in mice when challenged with L. monocytogene due to the elicitation of strong cellular immune responses [87]. Kon et al (2022) reported the development of an mRNA lipid nanoparticle (mRNA-LNP) vaccine against the plague, a highly infectious disease caused by the Gram-negative bacterium Yersinia pestis [88].…”
Section: Mrna Vaccine Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of an adjuvant led to the activation of invariant natural killer T (iNKT) cells and specific T cell responses. Experiments showed that immunization with the top vaccine candidate, LMON_0149, was able to confer protection in mice when challenged with L. monocytogene due to the elicitation of strong cellular immune responses [87]. Kon et al (2022) reported the development of an mRNA lipid nanoparticle (mRNA-LNP) vaccine against the plague, a highly infectious disease caused by the Gram-negative bacterium Yersinia pestis [88].…”
Section: Mrna Vaccine Candidatesmentioning
confidence: 99%
“…The use of an adjuvant led to the activation of invariant natural killer T (iNKT) cells and specific T cell responses. Experiments showed that immunization with the top vaccine candidate, LMON_0149, was able to confer protection in mice when challenged with L. monocytogene due to the elicitation of strong cellular immune responses [ 87 ].…”
Section: Current Preclinical and Clinical Development Of Next-generat...mentioning
confidence: 99%